DEVELOPMENT OF ASSESSMENT INSTRUMENTS ON CREATIVE THINKING SKILL IN ENVIRONMENTAL POLLUTION MATERIALS - Maulidia, Afifah; Sabtiawan, Wahyu Budi; Widodo, Wahono (Jurnal Penelitian Pendidikan IPA, 2020)
This study aims to produce instruments that are valid, reliable, and describe the skill to think creatively in environmental pollution material. The trial design of the study used Pre Experimental design with One Shot Case Study model. The subject of this study are 27 students of 7th Grade at SMPN 1 Sidoarjo. The research instrument on this study used students' sheet, questionare sheet, and test. This study used validity and reliablity teachniques. The reseach data were analyzed by descriptive quantitative and qualititative. The result of the research through theoritical validation showed that all questions were accepted and fit in. The results of the validity test of the assessment instrument showed that 6 items with sufficient validity and 6 items with high validity. Meanwhile, the reliability test value obtained at 0.796 in the high category. Based on the results, the category of fluency aspect is quite good with a percentage of 55.2%, the flexibility aspect percentage of 29.3% is not good category and an average overall aspect of 38.8% is in the poor category.This research can be used as an evaluation tool that can design learning to improve creative thinking skills.